2012
DOI: 10.1200/jco.2012.41.6677
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfractionated or Accelerated Radiotherapy in Lung Cancer: An Individual Patient Data Meta-Analysis

Abstract: Patients with nonmetastatic NSCLC derived a significant OS benefit from accelerated or hyperfractionated radiotherapy; a similar but nonsignificant trend was observed for SCLC. As expected, there was increased acute esophageal toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
120
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(132 citation statements)
references
References 39 publications
8
120
0
4
Order By: Relevance
“…In our study, we delivered the intended doses to the targets while respecting OAR constraints in most cases. Moreover, in a considerable number of cases, the limited doses delivered to the different OARs could open a window for dose intensification.With only 5% of grade 3 oesophagitis, our results compare favorably with those reported in the literature, 3,4 indicating that the dosimetric gain has a clinical impact on the incidence of AET. Even if acute oesophagitis has been considered reversible, it is responsible for treatment interruptions and dose reductions.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In our study, we delivered the intended doses to the targets while respecting OAR constraints in most cases. Moreover, in a considerable number of cases, the limited doses delivered to the different OARs could open a window for dose intensification.With only 5% of grade 3 oesophagitis, our results compare favorably with those reported in the literature, 3,4 indicating that the dosimetric gain has a clinical impact on the incidence of AET. Even if acute oesophagitis has been considered reversible, it is responsible for treatment interruptions and dose reductions.…”
supporting
confidence: 80%
“…With only 5% of grade 3 oesophagitis, our results compare favorably with those reported in the literature, 3,4 indicating that the dosimetric gain has a clinical impact on the incidence of AET. Even if acute oesophagitis has been considered reversible, it is responsible for treatment interruptions and dose reductions.…”
supporting
confidence: 80%
“…This might improve prognosis through lower locoregional recurrences and higher resection rates. A recent meta-analysis comparing modified RT schedules with conventional RT reported that patients with nonmetastatic NSCLC derived a significant OS benefit from accelerated or hyperfractionated radiotherapy (24).…”
Section: Neoadjuvant Hyperfractionated Radiotherapy With Chemotherapymentioning
confidence: 99%
“…A recent meta-analysis by Mauguen et al (15) evaluated ten trials including 2,000 patients and concluded that modifying the radiotherapy schedule by HyperFRT, ART or both resulted in an increase of overall survival. Employing altered fractionation reduced the risk of death by 12% and enhanced the 3-and 5-year survival rates, as an absolute overall survival increment was succeeded by 3.8% at 3 years and 2.5% at 5 years.…”
Section: Treatment Duration and Altered Fractionationmentioning
confidence: 99%